Media Sosial Sebagai Bentuk Represi Tokoh Margot dalam Film Searching (2018) - Masnia Rahayu (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The film Searching (2018) by Anesh Chaganty presents the reality of today's life, the life of real people who are very attached to activities in cyberspace through internet technology. All scenes in the film are depicted with computer/laptop screens, cctv, mobile phone cameras, and video-videos, so as to provide space for the audience as observers to see each scene presented. This study discusses how the personality structure of margot characters in the virtual world and the real world is reviewed from the interpretation of each scene through a narrative and cinematographic approach. The imbalance of personality structure for Freud will cause problems, so repression as a form of self-defense mechanism becomes an option for margot in self-balancing. The virtual world is a form of repression of Margot's character from all interactions and feelings faced in the real world. Social media plays a significant role in the process of individual development. The involvement of individuals in the real world and the virtual world is presented in the film Searching. There are differences in attitudes and feelings experienced by Margot's characters when interacting in the virtual world and the real world. The virtual world provides a space for him to explore himself, interact with his virtual friends, express his feelings, and keep all his memories of pleasure. This is contrary to the real world of Margot's character, in the film Margot limits her, keeps all her feelings and does not have good communication with her environment, including her own father.